Habitat use, trophic, and occurrence patterns of inpaichthys kerri and hyphessobrycon vilmae (Pisces: Characidae) in amazonian streams - Zeni, Jaquelini O. [UNESP]; Sensato-Azevedo, Luisa Martins [UNESP]; Dos Santos, Eduardo Fernando [UNESP]; Brejão, Gabriel Lourenço [UNESP]; Casatti, Lilian [UNESP] (FapUNIFESP (SciELO), 2020)
Fish ecomorphology and diet can help us to understand species response to impacts and coexistence patterns. Thus, we developed a comparative analysis of ecomorphology and diet of Inpaichthys kerri and Hyphessobrycon vilmae and tested for environmental variables that explain their abundance in headwater streams. We sampled streams from the Aripuanã River basin, Mato Grosso State, Brazil. We sampled environmental variables following a standardized protocol and used 30 and 80 individuals from each species to obtain ecomorphological attributes and feeding index, respectively. To identify environmental variables that influence species abundance, we developed generalized additive mixed models. Inpaichthys kerri presented broader and deeper caudal peduncles, more dorsal eyes, and larger fins, besides the lower consumption of aquatic insects, algae, and detritus when compared to H. vilmae. Inpaichthys kerri was more abundant in fast waters with little amounts of marginal grasses, conditions associated with more forested streams, while H. vilmae was more abundant in streams with more abundant marginal grasses from pasture. Deforestation in the Aripuanã basin threatens the persistence of I. kerri, since its optimal environmental conditions tend to be replaced by H. vilmae optimal conditions. Natural history helps us to understand species occurrence and represents a substantial contribution for more effective conservation measures.
Keywords: Deforestation; Diet; Ecomorphology; Marginal grasses; Species coexistence